2009
DOI: 10.1093/sleep/32.7.847
|View full text |Cite
|
Sign up to set email alerts
|

Sleep and Depression in Postpartum Women: A Population-Based Study

Abstract: Poor sleep was associated with depression independently of other risk factors. Poor sleep may increase the risk of depression in some women, but as previously known risk factors were also associated, mothers diagnosed with postpartum depression are not merely reporting symptoms of chronic sleep deprivation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

29
240
4
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 281 publications
(276 citation statements)
references
References 35 publications
29
240
4
3
Order By: Relevance
“…[8][9][10][11]13,[15][16][17]38 Although the statistic is not interpretable in our study (given the observed three-factor structure), we reported an overall Cronbach's α (0.57) so as to be consistent with the other studies. Several previous studies conducted among pregnant Australian and British women, 1,7 Norwegian postpartum women, 39 Australian adults, 40 and cancer patients in Greece 8 found that the removal of "sleep medication use" component improved the Cronbach's α for the PSQI. Jomeen et al reported that removal of this component (which was endorsed by < 3% of participants) contributed to the excellent general fit of a CFA model and recommended to remove this component from the global PSQI score calculation within the context of early pregnancy.…”
Section: Discussionmentioning
confidence: 95%
“…[8][9][10][11]13,[15][16][17]38 Although the statistic is not interpretable in our study (given the observed three-factor structure), we reported an overall Cronbach's α (0.57) so as to be consistent with the other studies. Several previous studies conducted among pregnant Australian and British women, 1,7 Norwegian postpartum women, 39 Australian adults, 40 and cancer patients in Greece 8 found that the removal of "sleep medication use" component improved the Cronbach's α for the PSQI. Jomeen et al reported that removal of this component (which was endorsed by < 3% of participants) contributed to the excellent general fit of a CFA model and recommended to remove this component from the global PSQI score calculation within the context of early pregnancy.…”
Section: Discussionmentioning
confidence: 95%
“…Residual pain from the birth can also prevent a mother from sleeping properly, which further increases risk of postnatal depression (Dørheim et al . 2009). It is unsurprising that mothers who have a difficult birth may both find breastfeeding more difficult and be at increased risk of PND.…”
Section: Discussionmentioning
confidence: 99%
“…To place these findings into perspective, the mean global score of 6.2 and the 55% prevalence of poor sleepers were similar to those found in a study of postpartum women (median and mean infant age of approximately 8 weeks), who had a mean global score of 6.3 and a 57.7% prevalence of poor sleepers. 23 Some studies involving undergraduate students, 4,5 medical students, 13,15 and pharmacy students 19 also used the PSQI as the standard sleep scale. While all of these studies reported the percentage of poor sleepers, only 3 of them reported mean global scores, 4,15,19 and only 1 reported mean component scores.…”
Section: Discussionmentioning
confidence: 99%